My Pay Day Educational Kit - Farrah Dina, Y.
This educational board game kit functions just like the famous Monoply game. However it is more specific towards teaching its Malaysian players, especially elementary and secondary school students on: • Financial planning – by playing this games, players will understand the importance of planning their monthly salary according to several important sections in life such as pay tuition fees, pay bills, buy groceries, visit parents at kampung, and entertainment. • Appreciating Malaysian and/Eastern culture and values – for instance, players are taught to set aside some of their monthly salary to visit their parents and families at their kampung,and to socialize with friends by giving them presents during their birthdays etc.